Clinical significance of serum soluble T‐cell immunoglobulin and mucin domain 3 levels in systemic sclerosis: Association with disease severity. Issue 2 (21st September 2016) - Chiba, Miki; Yanaba, Koichi; Hayashi, Mitsuha; Yoshihara, Yuki; Nakagawa, Hidemi
Abstract: T‐cell immunoglobulin and mucin domain 3 (TIM‐3) has been thought to play a crucial role in the negative regulation of immune responses. Here, we examined the levels of serum soluble TIM‐3 (sTIM‐3) in patients with systemic sclerosis (SSc) and evaluated the results with respect to the clinical features of the disease. Patients with diffuse cutaneous SSc (dcSSc) had higher levels of sTIM‐3 than those with limited cutaneous SSc and healthy individuals. Serum sTIM‐3 levels were positively correlated with the severity of skin sclerosis in early phase dcSSc. Moreover, serum sTIM‐3 levels were increased more often in patients with renal crisis and cardiac involvement than in those with normal sTIM‐3 levels. These results suggest that serum sTIM‐3 levels may be increased in patients with early phase dcSSc and associated with cardiac involvement and renal crisis. Measurement of serum sTIM‐3 may be useful for risk stratification in the early stage of the disease.